THE FOLD TEST: AN EIGEN ANALYSIS APPROACH - Tauxe L.; Watson G.S. (My University, 1994)
We combine eigen analysis and parameter estimation techniques for a newly constituted, more versatile fold test. The method is automatic, requiring no assumptions about the polarity or distribution of data, and gives confidence limits on the degree of unfolding required to produce the tightest grouping of data. We illustrate the method using several published data sets that show the tightest data groupings before, after and during correction for bedding tilt. The latter case is usually ascribed to acquisition of remanence during folding, but we show that this behavior can also arise from undetected multiple rotations. In our simulation, the beds undergo rotation about a vertical axis as well as a horizontal one, a case likely to occur in nature. These data, when rotated back to horizontal around what would be the observed strike, exhibit a peak in concentration at about 60% unfolding, very like the behavior of many published data sets. Thus, the origin of remanence in many such cases may not be syn-folding at all, but the behavior may purely be the result of an artifact of structural complications.